Modulation of macrophage inflammatory profile in pregnant nonobese diabetic (NOD) mice - Larocca, Luciana (2011)
During normal early pregnancy circulating monocytes are recruited to the maternal-placental interface where they differentiate to macrophages expressing different functional phenotypes for the maintenance of tissue homeostasis. Pregnancy in the nonobese diabetic (NOD) mouse model presents some pathological features in the pre-diabetic stage. The aim of this work was to analyze the functional profile of peritoneal macrophages faced with inflammatory and phagocytic stimuli in early pregnant pre-diabetic NOD mice and their modulation by vasoactive intestinal peptide (VIP). Pregnant NOD mouse macrophages showed no basal NFκB activation, lower IL-12 and nitrites production compared with the macrophages from non-pregnant NOD mice. Their pro-inflammatory aberrant response to LPS and apoptotic cell challenge was reduced and VIP inhibited macrophage residual deleterious responses to apoptotic cells. A functional phenotype switch in macrophages during pregnancy in NOD mice and a promoting effect of VIP towards this regulatory phenotype would be in line with the central role of macrophages in the maternal-placental dialogue.